Ruimtelijke differentiatie in het kiesgedrag van een stedelijke bevolking. De Leuvense verkiezingen 1987-1995 - Herman Van der Haegen (Belgeo)
The results of municipal and federal elections between 1987 and 1995 could be obtained in Leuven at neighbourhood level thanks to the notes of party witnesses in the polling stations. The results show that the traditional socio-economic structure of the city, with a strong concentration of working class people in the north and more middle class areas in the south, still determines voting behaviours. Moreover, these behaviours are explained, especially at local level, by the development of new neighbourhoods, the presumption of the Christian democratic party to break through the class structures and the presence of politicians with strong reputation. Political Parties: C.V.P.: Christian democrat; S.P.: socialist; V.L.D.: liberal; Agalev: green; V.U: Flemish nationalist; Vlaams Blok: ultra right populist